(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article examines the intricate relationship between beauty and morality in Oscar Wilde’s The Picture of Dorian Gray (1890). Through an aesthetic and ethical lens, the study explores how Wilde challenges Victorian moral conventions by presenting beauty as both a liberating and destructive force. Drawing on Lord Henry Wotton’s hedonistic philosophy, Dorian Gray’s moral degradation, and Basil Hallward’s idealistic vision, the article argues that Wilde deliberately deconstructs the Platonic equation of beauty with virtue. The portrait functions as a moral mirror, exposing the fatal consequences of privileging aesthetics over ethics. Textual analysis and close reading serve as primary methodologies.